Analysis of the Effect of Economic Growth, Average Years of Schooling, and Labor Force Participation Rate (TPAK) on Income Inequality in the Province of the Special Region of Yogyakarta - Erviani, Fhani; Setiawati, Ririt (Journal of Regional Economics and Development, 2026)
Income inequality remains a development issue in the Special Region of Yogyakarta Province, despite relatively good economic growth and human resource quality. This study aims to analyze the influence of economic growth, average years of schooling, and the labor force participation rate (TPAK) on income inequality for the period 2014–2023. The study used a quantitative approach with panel data regression across five regencies/cities in Yogyakarta Special Region. The results show that average years of schooling significantly influence income inequality, while economic growth and TPAK do not. Simultaneously, all three variables influence income inequality. These findings indicate that educational improvement and economic growth in the Special Region of Yogyakarta are not fully inclusive, necessitating policies that are more oriented toward regional equity.